Influence of viscosity enhancing agent on rheology and compressive strength of superplasticized mortars - Gołaszewski, Jacek (Journal of Civil Engineering and Management, 2009)
The results of investigation into the influence of Viscosity Enhancing Agents (VEA) on the rheological properties of mortars, different in cement and superplasticizer properties, are presented and discussed. Rheology results have been evaluated according to the Bingham model, which describes the rheology with 2 parameters: yield value and plastic viscosity. Rheological parameters were measured using Two‐Point Workability Test (TPWT). Additionally, the influence of VEA on compressive strength of mortars is presented. It was found that effects of VEA addition on rheological properties of mortars, as well as on compressive strength of mortars, significantly depend on cement and superplasticizer properties. Basic relation of influence of VEA on rheological properties and compressive strength of mortars in respect to cement and superplasticizer properties were presented and discussed. It is concluded that addition of VEA influences compatibility between cement and superplasticizer. Because addition of VEA may cause decrease in compressive strength, the assessment of compatibility of VEA ‐ cement ‐ superplasticizer system should be performed in relation not only to rheological properties, but also to compressive strength.SantraukaStraipsnyje pateikta ir išanalizuota klampą didinančių priedų įtaka skiedinių reologinėms savybėms. Skiediniai buvo ruošiami su įvairių savybių cementais ir superplastikliais. Reologijos tyrimų rezultatai įvertinti remiantis Binghamo modeliu. Reologinės savybės buvo tiriamos dviejų parametrų reometru (TPWT). Taip sudarytas naturalus šviežio skiedinio ir betono mišinio reologinės elgsenos būvis. Straipsnyje taip pat pateikti klampą didinančių priedų įtakos betono stipriui giuždant rezultatai. Nustatyta, kad klampą didinančių priedų poveikio efektas skiedinių reologinėms savybėms ir stipriui gniuždant iš esmės priklauso nuo cemento ir superplastiklių savybių.First Published Online: 14 Oct 2010Reikšminiai žodžiai: cementas, stipris gniuždant, betonas, skiedinys, reologija, superplastiklis, klampą didinantis priedas.